Implementasi Peraturan Pemerintah Nomor 94 Tahun 2021 Tentang Disiplin Pegawai Negeri Sipil di Pemerintah Kabupaten Kutai Barat - Kadarudin; Adi Wijaya; Sisilia (Collegium Studiosum Journal, 2020)
To realize reliable, professional and moral civil servants as government administrators who apply the principles of good governance, civil servants as elements of the State Apparatus are required to be loyal and obedient to Pancasila, the 1945 Constitution of the Republic of Indonesia, The Unitary State of the Republic of Indonesia and the government as well as being disciplined, honest, fair, transparent and accountable in carrying out their duties. The objectives are to ensure order and smooth implementation of the main tasks and functions of civil servants, to encourage performance improvements and changes in civil servants' attitudes and behavior, to increase civil servant discipline, to increase civil servants' responsibilities, to accelerate the process of change towards increasing professionalism in work. The author uses the library research method or literature review. This literature review research is conducting research from library books, magazines, journals and articles and sources from the internet that are relevant to the problems discussed. The following is a study based on Government Regulation Number 94 of 2021 concerning Civil Servant Discipline.